2016
DOI: 10.1007/s40685-016-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing those who do, might and will not invest in sustainable funds: a survey among German retail fund investors

Abstract: In this paper, we present the results of an online questionnaire among private German mutual fund investors. In an exploratory nature, we empirically analyze the differences between three groups: sustainable investors, conventional investors that are either generally interested or those that are not interested at all to invest in socially responsible (SR) funds. We provide evidence on motives and attitudes of these three investor groups, showing that SR fund investors are quite similar to those interested in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 56 publications
4
68
0
1
Order By: Relevance
“…Finally, the deep‐seated perception that a company's ESG performance is detrimental to financial performance poses a major impediment for institutional and private investors (Eccles & Kastrapeli, ; Paetzold & Busch, ; Wins & Zwergel, ). In addition to isolated investor experience of underperformance in more short‐term time frames and theme stocks, decades of dogma in education and business concerning the necessary distinction of shareholder and stakeholder interests could be one of the main explanations (Smith & Rönnegard, ; West, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the deep‐seated perception that a company's ESG performance is detrimental to financial performance poses a major impediment for institutional and private investors (Eccles & Kastrapeli, ; Paetzold & Busch, ; Wins & Zwergel, ). In addition to isolated investor experience of underperformance in more short‐term time frames and theme stocks, decades of dogma in education and business concerning the necessary distinction of shareholder and stakeholder interests could be one of the main explanations (Smith & Rönnegard, ; West, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We argue that the relation between altruistic values and behavior also holds for investment decisions. Socially responsible investors have higher donations to charity as well as higher social preferences (Jansson & Biel, ; Nilsson, ; Riedl & Smeets, ; Wiesel et al ., ; Wins & Zwergel, ). We argue that these investors will be intrinsically motivated (Andreoni, ; Beal, Goyen, & Philips, ) and engage in SRI because of their altruistic values.…”
Section: Hypothesesmentioning
confidence: 99%
“…Second, our work relates to the literature that uses surveys and experiments to analyze why people are socially responsible investors. Several studies provide evidence that prosocial attitudes and behavior are positively related to self‐reported SRI holdings (Gutsche, Köbrich León, & Ziegler, ; Nilsson, ; Wins & Zwergel, ). In line with this evidence, Riedl and Smeets () find that social preferences are positively related to holdings in SRI mutual funds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new feature of this research is the application of this technique to a medium‐term savings product: savings deposits. In the literature on SRI, there are studies focused on the purchasing of investment funds (Barreda‐Tarrazona, Matallín‐Sáez, & Balaguer‐Franch, ; Lewis & Mackenzie, ; Nilsson, ; Nilsson, ; Nilsson, Nordvall, & Isberg, ; Sandberg & Nilsson, ; Tippet, ; Wins & Zwergel, ) and the purchase of shares (Beal & Goyen, ; Clark‐Murphy & Soutar, ; Consolandi, Innocenti, & Vercelli, ; Nakai, Honda, Nishino, & Takeuchi, ). However, no studies using this approach and focussing on savings deposits have been found, despite this being one of the most popular financial products in the Spanish market (Bank of Spain, ; Valor et al, ).…”
Section: Introductionmentioning
confidence: 99%